2022
DOI: 10.1007/s00402-022-04601-3
|View full text |Cite
|
Sign up to set email alerts
|

Patients successfully lose body weight after primary total knee arthroplasty but not more than a matched general population

Abstract: Introduction High BMI is associated with increased risk for knee osteoarthritis, ultimately necessitating total knee arthroplasty (TKA). The aim of this retrospective study was to (1) analyse the amount of postoperative long-term weight loss as reflected by BMI change in TKA patients, (2) identify factors associated with increased change in BMI, and to (3) compare changes with BMI trends of a general population. Materials and methods Overall, 298 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Whether patients tend to lose weight after TJA is controversial. Studies have shown a significant drop in BMI after total knee arthroplasty (TKA), with patients with higher BMIs more likely to lose weight postoperatively 22 , and 46% of patients lose weight after TKA 23 . Conversely, Coelho et al found that 68% of patients did not have a change in weight at 1 year 24 .…”
Section: Beneficencementioning
confidence: 99%
“…Whether patients tend to lose weight after TJA is controversial. Studies have shown a significant drop in BMI after total knee arthroplasty (TKA), with patients with higher BMIs more likely to lose weight postoperatively 22 , and 46% of patients lose weight after TKA 23 . Conversely, Coelho et al found that 68% of patients did not have a change in weight at 1 year 24 .…”
Section: Beneficencementioning
confidence: 99%